Integrated Information System to Improve Production Efficiency and Inventory Accuracy in the F&B Industry - Dessyty Dessyty; Verawati Verawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The Food and Beverage (F&B) industry operates in a highly dynamic environment characterized by rapid production cycles, fluctuating customer demand, limited processing time, and perishable raw materials. These conditions require companies not only to maintain efficient production activities but also to ensure accurate inventory management in order to minimize waste and operational disruptions. In many cases, delays in information flow and inaccurate stock records can negatively affect production continuity and overall business performance. Therefore, an integrated information system is essential to support effective coordination between operational divisions. This study aims to develop an integrated information system that connects production activities with inventory management processes. The system functions not only as a data recording platform but also as an operational integration tool that enables continuous and real-time information exchange across departments. By implementing a structured material requirement mechanism, the system is able to calculate raw material needs efficiently and automatically update inventory data whenever production activities occur. This integration ensures that information is distributed consistently throughout the operational process. The system was developed using an object-oriented approach to provide flexibility, scalability, and ease of future development. The implementation results indicate significant improvements in inventory data accuracy, reduced recording errors, and faster operational response times. Overall, the integrated information system contributes to enhancing production efficiency, maintaining inventory accuracy, and supporting operational stability within the F&B industry.